2022
DOI: 10.15585/mmwr.mm7148e1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bivalent mRNA Vaccines in Preventing Symptomatic SARS-CoV-2 Infection — Increasing Community Access to Testing Program, United States, September–November 2022

Abstract: On November 22, 2022, this report was posted as an MMWR Early Release on the MMWR website (https://www.cdc.gov/mmwr).On September 1, 2022, bivalent COVID-19 mRNA vaccines, composed of components from the SARS-CoV-2 ancestral and Omicron BA.4/BA.5 strains, were recommended by the Advisory Committee on Immunization Practices (ACIP) to address reduced effectiveness of COVID-19 monovalent vaccines during SARS-CoV-2 Omicron variant predominance (1). Initial recommendations included persons aged ≥12 years (Pfizer-Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
139
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 155 publications
(153 citation statements)
references
References 7 publications
13
139
0
1
Order By: Relevance
“…This study found that the current bivalent vaccines were about 30% effective overall in protecting against infection with SARS-CoV-2, when the Omicron BA.4/BA.5 lineages were the predominant circulating strains. The magnitude of protection afforded by bivalent vaccination was similar to that estimated in a recent study using data from the Increasing Community Access to Testing (ICATT) national SARS-CoV-2 testing program [16].…”
Section: Discussionsupporting
confidence: 79%
“…This study found that the current bivalent vaccines were about 30% effective overall in protecting against infection with SARS-CoV-2, when the Omicron BA.4/BA.5 lineages were the predominant circulating strains. The magnitude of protection afforded by bivalent vaccination was similar to that estimated in a recent study using data from the Increasing Community Access to Testing (ICATT) national SARS-CoV-2 testing program [16].…”
Section: Discussionsupporting
confidence: 79%
“…Bivalent COVID-19 booster vaccines were developed to improve protection against circulating Omicron sublineages because of immune escape potentially associated with these subvariants and waning of monovalent vaccine-conferred protection over time ( 7 ). Real-world data suggest that bivalent boosters provide a modest degree of protection against symptomatic infection among adults compared with receipt of 2, 3, or 4 doses of monovalent vaccines only ( 8 ). Results from this study also demonstrate protection against ED/UC encounters and hospitalization during a period when BA.5 and other Omicron sublineage viruses predominated in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…However, early follow-up of the impact of bivalent boosters in the US have demonstrated an added benefit over monovalent boosters. 30 One of the major limitations of our work is that it was not possible to distinguish the combined effects of infection-and vaccine-induced immunity. The vaccine effectiveness data to which we fit our model is based on the full population of England with effectiveness estimates obtained by comparing outcomes according to vaccine dose against those with no prior vaccination.…”
Section: Discussionmentioning
confidence: 98%